Features of building physical therapy programs to improve mobility in the cervical-thoracic spine - Kravchenko, Tamara; Antonova-Rafi , Yuliya (The Ukrainian Scientific Medical Youth Journal, 2024)
the article discusses the peculiarities of developing physical therapy programs to improve mobility in the cervical-thoracic spine. The author examines the relationship between neck pain and thoracic spine conditions, providing approaches to effectively reduce pain and increase mobility. The article reveals specific methods and tools that contribute not only to pain relief but also to active restoration of mobility in both parts of the spine. The author takes into account the individual characteristics of patients, offering a personalized approach to the physical therapy program. The proposed methodology helps to improve the general condition of the body, psycho-emotional state, mobility in the thoracic spine, and reduce pain in the neck, shoulder girdle, and thoracic spine. In order to evaluate the effectiveness of the developed physical therapy program for patients with neck pain and impaired mobility of the thoracic spine (kyphotic posture), a study was conducted on 5 patients who were observed at the Institute of Vertebrology and Rehabilitation clinic in Kyiv. Kyiv.